2017
DOI: 10.1161/strokeaha.116.014660
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery for ARUBA Trial (A Randomized Trial of Unruptured Brain Arteriovenous Malformation)–Eligible Unruptured Brain Arteriovenous Malformations

Abstract: Background and Purpose-The management of unruptured brain arteriovenous malformations (ubAVMs) remains controversial despite ARUBA trial (A Randomized Trial of Unruptured Brain Arteriovenous Malformation), a controlled trial that suggested superiority of conservative management over intervention. However, microsurgery occurred in only 14.9% of ARUBA intervention cases, raising concerns about the study's generalizability. Our purpose was to evaluate whether, in a larger ARUBA-eligible ubAVM population, microsur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 42 publications
1
59
1
1
Order By: Relevance
“…12 Hence the supposed negative impact of surgery on the outcome of unruptured AVMs is certainly not generalizable. 24 Moreover, the reported complication rates of any treatment were higher than expected; these are very different results from those previously reported in other cohorts [24][25][26][27][28][29][30] and were not explained by the ARUBA investigators. Furthermore, no data on obliteration rates were provided.…”
Section: Microsurgery As the Standard Of Care For Pfavmscontrasting
confidence: 68%
“…12 Hence the supposed negative impact of surgery on the outcome of unruptured AVMs is certainly not generalizable. 24 Moreover, the reported complication rates of any treatment were higher than expected; these are very different results from those previously reported in other cohorts [24][25][26][27][28][29][30] and were not explained by the ARUBA investigators. Furthermore, no data on obliteration rates were provided.…”
Section: Microsurgery As the Standard Of Care For Pfavmscontrasting
confidence: 68%
“…This study found that among patients aged 16 years or older, the conservative management was associated with better clinical outcomes for up to 12 years compared with intervention . Numerous centers have since reported superior safety profiles with treatment . The optimal treatment remains controversial.…”
Section: Current Treatments and Future Directions/developments Prospementioning
confidence: 87%
“…113 Numerous centers have since reported superior safety profiles with treatment. [114][115][116][117][118][119][120] The optimal treatment remains controversial.…”
Section: Current Tre Atments and Future Direc Tions/de Velopments Pmentioning
confidence: 99%
“…Despite the fact that we did not encounter haemorrhagic complications related to the application of Bdirty coagulation^technique, our series is relatively small and does not allow us to make an unambiguous statement about the effectiveness of the method. Perioperative bleeding complications after surgical treatment vary from 0 to 12.8% in different series [4,5,15]. As we analysed only cases with available high-definition quality videos, our series included only 35 cases that were performed during the last 5 years.…”
Section: Discussionmentioning
confidence: 99%